בבקשה לפתור q 5?

בבקשה לפתור q 5?
Anonim

תשובה:

ראה למטה.

הסבר:

יש לנו, # xolor (לבן) (xxx) a ^ (2x - 3) * b ^ (2x) = a (6-x) * b ^ (5x) #

#rArr a ^ (2x - 3) / a ^ (6-x) = b ^ (5x) / b ^ (2x) #

פשוט לשנות את # a # ו # b # על צדדיו.

#rArr a ^ (2x - 3) - (6 - x)) = b ^ (5x - 2x) # # כפי ש # a ^ (m-n) = a ^ m / a ^ n #

#rArr a ^ (2x - 3 - 6 + x) = b ^ (3x) #

#rArr a ^ (3x - 9) = b ^ (3x) #

#rArr (a ^ (x - 3)) ^ 3 = (b ^ x) ^ 3 # כפי ש, # (x ^ m) ^ n = x ^ (mn) #

#rArr a ^ (x - 3) = b ^ x #

#rArr a ^ x / a ^ 3 = b ^ x # כפי ש # a ^ (m-n) = a ^ m / a ^ n #

#rArr a ^ x / b ^ x = a ^ 3 # טרנספוזיציה שוב

#rArr (a / b) ^ x = a ^ 3 # כפי ש # (a / b) ^ m = a ^ m / b ^ m #

#rArr log (a / b) ^ x = log a ^ 3 # לוקח # log # בשני הצדדים

#rArr x log (a / b) = 3 log # כפי ש #log a ^ x = x log #

#rArr 3 log a = x log (a / b) #

לפיכך הוכח.